What do patients receiving palliative care for cancer and their families want to be told? A Canadian and Australian qualitative study. Issue 7452 (19th May 2004) - Kirk, Peter; Kirk, Ingrid; Kristjanson, Linda J
Abstract : Objective To obtain feedback from patients receiving palliative care and their relatives from various ethnic backgrounds about their experiences of the disclosure process and their satisfaction with information sharing during the illness. Design A qualitative study with semistructured single interviews. Setting Perth, Western Australia, and Winnipeg, Manitoba, Canada. Participants 72 participants registered with palliative care: 21 patient-family dyads in Perth and 14 dyads and 2 patients in Winnipeg. Results Participants described their experiences in great detail. The analysis indicates that in information sharing the process is as important as the content. The timing, management, and delivery of information and perceived attitude of practitioners were critical to the process. This applied to information interactions at all stages of the illness. Main content areas mentioned related to prognosis and hope. Hope can be conveyed in different ways. Secondary information from various sources is accessed and synthesised with the primary information. All patients, regardless of origin, wanted information about their illness and wanted it fully shared with relatives. Almost all patients requested prognostic information, and all family members respected their wishes. Information was perceived as important for patient-family communication. Information needs of patient and family changed and diverged as illness progressed, and communication between them became less verbally explicit. Conclusions Information delivery for patients needs to be individualised with particular attention to process at all stages of illness. Patients and families use secondary sources of information to complement and verify information given by health carers.